HUBUNGAN DUKUNGAN SOSIAL TERHADAP MOTIVASI BELAJAR MAHASISWA - Mufidah, Vika Nurul; Fadilah, Nadiah Nurli (Mozaic : Islam Nusantara, 2023)
Every student needs motivation when studying, including students at Universitas Nahdlatul Ulama Indonesia. One thing that can influence learning motivation is social support. This research aims to determine the relationship between social support and learning motivation of first semester students at Universitas Nahdlatul Ulama Indonesia. A total of 142 students were sampled in this research. The research results show that there is a positive and significant relationship between social support and learning motivation. Thus, it can be concluded that social support can increase the learning motivation of first semester students at Universitas Nahdlatul Ulama Indonesia.